What to do about African Honey Bees: A Consumer Guide - Michael K. O’Malley; James D. Ellis; Anita S. Neal (EDIS)
The general public can take several steps to avoid encountering honey bee swarms or colonies. The first and most important step is for citizens to educate themselves and their families about the African honey bee (AHB). This revised 3-page fact sheet provides links to valuable resources, definitions of key terms, and touches on general precautions and bee-proofing. Written by M. K. O’Malley, J. D. Ellis and A. S. Neal, and published by the UF Department of Entomology and Nematology, October 2014. (Photo: Scott Bauer, USDA/ARS)